ANALISIS KEMAMPUAN PEMECAHAN MASALAH MELALUI PEMBELAJARAN BERBASIS MASALAH DENGAN TEKNIK KLARIFIKASI NILAI - Yeyen Herlina (CV. ADIBA AISHA AMIRA, 2024)
The process of thinking in solving problem needs teachers’ attention to help students in developing problem solving ability. This study aims to gain effective math learning tools and analyze the problem-solving ability in terms of troubleshooting steps based Polya. This research is mixed method. On quantitative methods generate mathematical learning is declared effective. In the qualitative method, problem-solving ability and VIIIF VIIID graders determined using an early test problem solving abilities. Each category of problem-solving ability is taken 2 students for research subjects. Students were given Problem Solving Tests (TPM) and interviewed as triangulation. PMAK subjects and PMAL subjects had good abilities in problem solving. Problem solving ability PMTK subjects and PMTL subjects were quite well. However, the two subjects could not arranged problem solving with different steps and not able to recheck the results of problem solving. PMBK subjects got some constraints to use prerequisite knowledge, applied appropriate strategies to solve problems, and reflected problem solving process using Polya steps. PMBL subjects had not been able to meet almost all indicators of problem solvin